The DarkSide Multiton Detector for the Direct Dark Matter Search. (20th January 2015) - Aalseth, C. E.; Agnes, P.; Alton, A.; Arisaka, K.; Asner, D. M.; Back, H. O.; Baldin, B.; Biery, K.; Bonfini, G.; Bossa, M.; Brigatti, A.; Brodsky, J.; et al.
Abstract : Although the existence of dark matter is supported by many evidences, based on astrophysical measurements, its nature is still completely unknown. One major candidate is represented by weakly interacting massive particles (WIMPs), which could in principle be detected through their collisions with ordinary nuclei in a sensitive target, producing observable low-energy (<100 keV) nuclear recoils. The DarkSide program aims at the WIPMs detection using a liquid argon time projection chamber (LAr-TPC). In this paper we quickly review the DarkSide program focusing in particular on the next generation experiment DarkSide-G2, a 3.6-ton LAr-TPC. The different detector components are described as well as the improvements needed to scale the detector from DarkSide-50 (50 kg LAr-TPC) up to DarkSide-G2. Finally, the preliminary results on background suppression and expected sensitivity are presented.